2017
DOI: 10.3389/fmicb.2017.01933
|View full text |Cite|
|
Sign up to set email alerts
|

Pathogenicity of Human ST23 Streptococcus agalactiae to Fish and Genomic Comparison of Pathogenic and Non-pathogenic Isolates

Abstract: Streptococcus agalactiae, or Group B Streptococcus (GBS), is a major pathogen causing neonatal sepsis and meningitis, bovine mastitis, and fish meningoencephalitis. CC23, including its namesake ST23, is not only the predominant GBS strain derived from human and cattle, but also can infect a variety of homeothermic and poikilothermic species. However, it has never been characterized in fish. This study aimed to determine the pathogenicity of ST23 GBS to fish and explore the mechanisms causing the difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Using BlastN tools, a search for prophages similar to 12/111phiA identified 10 Javan-like prophages from the genome of Streptococci [ 50 ], and 12/111phiA-like features in the genomes of 13 GBS strains ( Table S5 ; Figure 2 ) and 10 non-GBS Streptococci , including S. urinalis , S. constellatus , S. canis , and S. equi . In particular, prophage MR1-Z1-201_Phi carried by a ST23 GBS, isolated in the U.K. from a seal, shared 93% identity (78% cover) with 12/111phiA ( Figure 2 ) and yielded three genes identical to the three ORFs endonuclease , yafQ , and relB carried by 12/111phiA (100% identity; 100% cover) [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using BlastN tools, a search for prophages similar to 12/111phiA identified 10 Javan-like prophages from the genome of Streptococci [ 50 ], and 12/111phiA-like features in the genomes of 13 GBS strains ( Table S5 ; Figure 2 ) and 10 non-GBS Streptococci , including S. urinalis , S. constellatus , S. canis , and S. equi . In particular, prophage MR1-Z1-201_Phi carried by a ST23 GBS, isolated in the U.K. from a seal, shared 93% identity (78% cover) with 12/111phiA ( Figure 2 ) and yielded three genes identical to the three ORFs endonuclease , yafQ , and relB carried by 12/111phiA (100% identity; 100% cover) [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…ST23 has been identified as a dominant strain commonly associated with invasive GBS infections (Chang et al, 2014;Ezhumalai et al, 2020). Another study found that human ST23 GBS can be pathogenic to fish, possibly due to phage recombination (Wang et al, 2017). In conclusion, detailed history and clinical suspicion are the critical factors to diagnose GBS infections in tenosynovitis.…”
Section: Discussionmentioning
confidence: 93%
“…The invasive serotype III sequence type 283 (ST283) Streptococcus agalactiae was identified as the causative organism, with the same strain identified among farmed freshwater fish used for food preparation. [60][61][62] The outbreak stopped after affected fish imports into Singapore were banned and stricter rules were established governing raw fish dishes. 60 However, there have been other, smaller outbreaks of human meningitis in Hong Kong and Southeast Asia involving the ST283 strain, suggesting a potential public health threat of this foodborne zoonosis in Asia.…”
Section: Zoonotic Outbreak From Contaminated Raw Fish: Group B Streptmentioning
confidence: 99%